Have Autocrats Governed for the Long Term? - Millemaci, Emanuele; Monteforte, Fabio; Temple, Jonathan R. W. (Kyklos, 2025)
The short answer is: probably not. We infer the priorities of national governments from observed outcomes, constructing a statistical proxy for long‐term benevolence. Using data between 1960 and 2019 for more than 100 countries, we show that, on average, democracies score more highly on our measure. We then investigate whether variation in long‐term benevolence can explain the 'autocratic gamble'—the well‐known tendency for growth rates to vary more widely across autocracies than across democracies. We show that the distribution of long‐term benevolence under democracy first‐order stochastically dominates its distribution under autocracy. Put differently, although there is an autocratic gamble in growth rates, there is no autocratic gamble in wider development outcomes. The rapid growth seen in some autocracies probably originates in regime self‐interest rather than unusually benevolent leadership.